Effect of Compressive Strain of Brake Pads on Brake Noise - Yihong Gu; Yucheng Liu; Congda Lu; Shugen Hu; Xiaowen Song (Shock and Vibration)
Brake noise, a principal component of vehicle noise, is among the most critical measures of vehicle quality. The perceived quality of cars can be improved by reducing brake noise; therefore, vehicle manufacturers are extensively investigating the influencing factors, generating mechanism, and solutions of brake noise. Compressive strain is one of the most influential performance parameters of a brake pad and can be adjusted by regulating the material elastic modulus and by modifying the shape of the brake lining. In this study, the compressive strain of a brake pad was adjusted through four methods, and the noise characteristics of brake pads with different elastic modulus, section outlines, lining widths, and chamfers were studied through finite element analysis and the complex-eigenvalue method. The effects of compressive strain of a brake pad on brake noise were examined, and an optimized brake-pad scheme was developed. A dynamometer test conducted to validate the effectiveness of the optimized scheme confirmed a clear alleviation in brake noise.